Gas‐phase chemistry and reactive‐ion etching kinetics for silicon‐based materials in C4F8 + O2 + Ar plasma. Issue 7 (17th May 2021) - Lee, Byung Jun; Efremov, Alexander; Kwon, Kwang‐Ho
Abstract: In this study, we investigated the effects of C4 F8 /O2 and Ar/O2 component ratios in C4 F8 + O2 + Ar gas system on plasma parameters, gas‐phase chemistry, and etching kinetics for Si, SiO2, and Si3 N4 under the condition of inductively coupled radiofrequency (13.56 MHz) plasma. The use of plasma diagnostics by Langmuir probes, together with the zero‐dimensional plasma modeling, allowed one to compare two different gas mixing regimes in respect to (a) electrons‐ and ions‐related plasma parameters; (b) steady‐state densities of plasma active species; and (c) formation and decay kinetics for F atoms and polymerizing radicals. It was shown that variations in both C4 F8 /O2 and Ar/O2 mixing ratios result in nonmonotonic (with maximums at ∼10% to 15% O2 ) Si, SiO2, and Si3 N4 etching rates as well as in opposite changes in corresponding effective reaction probabilities. The model‐based analysis of etching mechanisms allowed one to suggest that the net effect from all heterogeneous (i.e., appeared on the etched surface) interaction pathways may be controlled either by the fluorocarbon radical flux (in the case of Ar/O2 mixing ratios at constant fraction of C4 F8 ) through the polymer film thickness or by the O atom flux (in the case of C4 F8 /O2 mixing ratios at constant fraction of Ar) through the balance of adsorption sites. Abstract : Etching kinetics and fluxes of active species in C4 F8 + Ar plasma.